Retrospective evaluation of multiplex PCR panel results from CSF samples in a university hospital - Funda Şahin; Nida Özcan; Erdal Özbek; Selahattin Atmaca; Hakan Temiz (Northwestern Medical Journal)
Aim: Given the significant mortality and sequelae due to meningitis, rapid diagnosis and initiation of treatment have a major impact on patient outcomes. In many cases of meningitis/meningoencephalitis, empirical treatment should be initiated immediately. This empirical treatment regimen is initiated based on the cumulative antibiotic susceptibility results in the region. The aim of our study was to retrospectively determine the causative agents in cerebrospinal fluid samples of patients who received a presumptive diagnosis of meningitis, using Multiplex Polymerase Chain Reaction (PCR) tests.